The elasmobranchs of Malpelo Flora and Fauna Sanctuary, Colombia. Issue 5 (9th September 2021) - Bessudo, Sandra; Ladino, Felipe; Becerril‐García, Edgar Eduardo; Shepard, Charles M.; Salinas‐De‐León, Pelayo; Hoyos‐Padilla, Edgar Mauricio
Abstract: Management and conservation actions in marine‐protected areas require baselines for monitoring threatened marine fauna such as elasmobranchs. This article provides evidence of the occurrence of 34 species of elasmobranchs (21 sharks and 13 batoids) in the Malpelo Flora and Fauna Sanctuary, Colombia, including five new records of sharks and three of rays. From 1987 to 2021, new records were obtained by underwater visual census using SCUBA, manned submersibles and deep‐ocean cameras to depths of up to 2211 m. Of the recorded species, 21 are considered as threatened taxa (64%) by the IUCN, making the Malpelo Flora and Fauna Sanctuary an essential conservation area for this highly threatened group of species.